Challenges of international law integration: Protecting rights of Rohingya refugees in Aceh - Yordan Gunawan; Muhammad Farel Reyhan; Labib Dianatadilaga Jayapraja (Jurnal Hukum Novelty, 2026)
Introduction to the Problem: Indonesia continues to face significant legal and policy challenges in protecting Rohingya refugees arriving in Aceh Province, particularly due to the country’s non-ratification of the 1951 Refugee Convention and the absence of comprehensive national refugee legislation. Purpose/Study Objectives: This article aims to analyze Indonesia’s legal and policy framework in protecting Rohingya refugees, with a specific focus on the integration of international refugee law, compliance with humanitarian principles, and the implications of the “safe third country” policy. Design/Methodology/Approach: The study employs a qualitative, normative legal research method, using a doctrinal approach, and examines national statutory regulations, presidential decrees, and relevant international legal instruments, including the 1951 Refugee Convention, the 1967 Protocol, and the principle of non-refoulement. Findings: The findings indicate that Indonesia’s refusal to ratify the 1951 Refugee Convention and the lack of clear statutory guidelines create legal gaps that hinder effective refugee protection. These gaps place Rohingya refugees in a state of legal uncertainty and weaken the practical implementation of humanitarian principles, particularly the principle of non-refoulement, within Indonesia’s “safe third country” policy framework. Paper Type: Research Article